GELIAT INOVASI PENDIDIKAN ISLAM (SEKOLAHISASI PESANTREN DAN PESANTRENISASI SEKOLAH DI PONDOK PESANTREN TEBUIRENG JOMBANG) - Chusnul Chotimah (LP2M IAIN Tulungagung, 2018)
Boarding school faces several challenges in order to maintain its existence, one of which is the usefulness of students in the community, and competition with non pesantren output. However, the boarding school also innovations in the form of public school founded in boarding schools so that students or graduates of the boarding school has a graduate diploma equivalent to non pesantren. In addition, the function of the public schools as well as improving the quality of output boarding. In addition, efforts to require students to stay in the boarding school is also important, because schools are a good place to inheritance traditions. So it is expected such learners on boarding school resulted in the formation of strong Islamic character on self-learners. Keyword: Islamic Education, Pesantren, School